Como lo hacía Mamá: cocina tradicional campesina colombiana -un homenaje al conocimiento campesino- (2020)
Como lo hacía mamá is a design project around the Tigridia Pavonia or Maravillas and its sustainable reintegration at El Paraiso farm located in the municipality of Cachipay, Cundinamarca, Colombia. The document shows the process carried out for the recovery of the Maravillas, Tigridia Pavonia, through the dissemination and promotion of its culinary value for future sowing. The importance of the Tigridia within an ecosystem is first identified, the way in which it interacts with the human being and in what way this same is capable of generating a community around the plant. In the first place, the current state of the plant was analyzed, recognizing the practices and relevant actors within the landscape. As a result of this, the demarcation of the application and place of the intervention process is obtained. Based on this, a tool is proposed with which to promote the agricultural production of wonders for self-consumption, finally the recovery process begins with a group of women from the community.